Program Edukasi Bank Sampah Melalui Inovasi Pujasalika kepada Masyarakat Desa Kalisalak Kecamatan Batang Provinsi Jawa Tengah - Alfa Reza Triananda; Selvia Junita Praja (Civitas Consecratio: Journal of Community Service and Empowerment, 2022)
The COVID-19 pandemic brings impacts on various sectors in life. One of the sectors which get the most affected is the economic sector. In the second quarter of 2020, Indonesia's economic growth significantly decreased, reaching -5.32%. The efforts that can be made to revive the economic sector during the pandemic are by making the innovations. The innovations that organized by the Kalisalak Village Government in order to revive the economic sector are Pujasalika and Bank Sampah. The purpose of Community service activity is to give people of Kalisalak Village more education about Bank Sampah and Pujasalika so that the innovations that have been made by the Kalisalak Village Government can be successful. The results of this community dedication activity, people become more aware with the innovations that made by the Kalisalak Village government and are interested in participating in Bank Sampah program. Bank Sampah and Pujasalika are very good innovations in order to fix the economic sector by involving more rural communities in its implementation, especially in Bank Sampah innovation.